2016
DOI: 10.1515/bhk-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

The development of anterior-posterior spinal curvature in children aged 7–12 years

Abstract: SummaryStudy aim: Body posture changes depend on numerous factors. The purpose of this study was to assess the changes in posture in the sagittal plane of children aged 7-12 years. Material and methods: Postural changes were determined by assessing the postural parameters in the sagittal plane. The measurements were recorded in children attending selected primary schools. In total, 562 subjects were included in the study, including 278 boys and 284 girls. The body posture was assessed photogrammetrically based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our study did not confirm that conclusion. Drzał-Grabiec et al also reported that spinal curvatures changed with age [3].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study did not confirm that conclusion. Drzał-Grabiec et al also reported that spinal curvatures changed with age [3].…”
Section: Discussionmentioning
confidence: 94%
“…LLA was statistically significant only in groups of 15-and 16-year-olds. Thoracic kyphosis was [20], Drzał-Grabiec et al [3], and Poussa et al [16], but they do not agree with the results of Mac-Thiong et al, in which there was no significant difference between boys and girls aged 4-18 [12]. The results of Szczepanowska-Wołowiec et al, who used the same measurement technique, also confirmed the variation of different posture types based on gender, and revealed an increase of thoracic kyphosis in boys [19].…”
Section: Discussionmentioning
confidence: 97%
“…Sagittal spinal alignment in the sitting position is different than that in the standing position and it changes as the child grows [5]. When sitting, there is a posterior tilt of the pelvis and a verticalization 2 of 18 of the sacrum [6,7], which results in a more or less pronounced loss of the lumbar lordosis with regard to standing [6, [8][9][10][11][12]. Under these conditions, the intervertebral discs can suffer compression in the anterior part of the fibrous ring, a posterior migration of the nucleus [13,14], and an increase in the intradiscal pressure [13,15], which causes damage to the intervertebral discs [16] and increases the tension in the passive elements of the posterior part of the spine [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to the data reported in the literature, the rate of overweight and obesity in children is consistently increasing 15. A similar situation is observed in the case of postural defects 16. In previously conducted studies numerous authors have investigated factors affecting obesity or postural defects, though usually focusing on these problems separately 15 17 18.…”
Section: Introductionmentioning
confidence: 54%